Causes of health inequities. Issue 3 (June 2022) - Lee, Allison; Padilla, Cesar
Abstract : Purpose of review: A renewed focus on U.S. racial and ethnic maternal health disparities has arisen following high-profile incidents of police violence and antiracism protests which coincided with the coronavirus disease 2019 pandemic, which has exerted a disproportionate effect on minority communities. Understanding the causes of disparities is pivotal for developing solutions. Recent findings: Social determinants of health must be addressed during clinical care; however, race must be used with caution in clinical decision-making. Medicaid expansion has been associated with a decrease in severe maternal morbidity and mortality, especially for racial and ethnic minority women. Indirect obstetric causes are the leading cause of maternal death. Summary: Policy-level changes and investment in marginalized communities are required to improve access to quality maternity care at all stages, including preconception, interconception, prenatal, intrapartum and postpartum for 12 months after delivery. Improvements in hospital quality and implementation of evidence-based bundles of care are crucial. Clinicians should receive training regarding susceptibility to implicit bias. To support the research agenda, better collection of race and ethnicity data and anesthesia care indicators is a priority (see Video, Supplemental Digital Content 1 {Video abstract that provides an overview of the causes racial and ethnic disparities in maternal health outcomes.} http://links.lww.com/COAN/A85 ).